Peptostreptococcus anaerobius is a potential diagnostic biomarker of colorectal cancer: P. anaerobius is linked to prognosis of colorectal cancer - Zhang, Yuchao; Fan, Kaihu; Li, Linping; He, Jialun; Sun, Ying (Cellular and Molecular Biology, 2023)
Accumulating evidences have shown that Peptostreptococcus anaerobius (P.a) is abundantly enriched in the fetus of colorectal cancer (CRC) patients. P.a is reported able to invade colorectal tissues. This study intends to uncover the clinical significance of P.a in CRC. Mucosal tissues collected from CRC cases (n=109) and precancerous healthy ones (n=65) were subjected to the determination of the absolute copy number of P.a by droplet digital PCR. The positive rate of P.a in mucosal tissues of CRC and healthy ones was 79.8% (87/109), and 55.4% (36/65), respectively. The average absolute copy number of P.a in them was 2.3 copy/ng DNA, and 0.32 copy/ng DNA, respectively. The abundance of P.a in mucosal tissues of CRC, and age and TNM staging of CRC cases were correlated to its survival. The abundance of P.a in CRC cases was remarkably correlated to the relative level of SQLE. The abundance of P.a can be monitored to predict the prognosis of CRC.